Karakteristik Aktivitas Pedagang Kaki Lima di Ruang Publik Kota pada Taman Tirto Agung, Kecamatan Banyumanik, Semarang - Retno Widjajanti (Department of Urban and Regional Planning, Faculty of Engineering, Diponegoro University, 2018)
Street vendors grow in urban areas, due to the narrowness of employment in the formal sector. Street vendors often occupy public spaces such as roadside, sidewalks, parks and fields. Ironically, the existence of street vendors is often considered the government as source of problem. One of them street vendors in the Taman Tirto Agung, Banyumanik District, street vendor activities growing in the sidewalks and parks. The existence of street vendors has changed the function of the park and degrade the visual quality of the space. Actually this problem arises because there is no exact location determination for street vendors by considering the characteristics of street vendors. The purpose of this research is to find activity characteristic of street vendor in Taman Tirto Agung. This research uses quantitative method. The results showed that the characteristics of street vendors in Taman Tirto Agung were influenced by diverse types of activity residential, commercial and recreation; a variety of merchandise that varies according to the needs of the surrounding community (raw materials, food/beverages, toys, services), means of trade is carts, tent carts, bicycles with baskets, car/motorcycle, umbrella table/tent tables), and time of activity (06.00-24.00) follow the time of regional activity (04.30-24.00).